A model to measure the brand loyalty for fast moving consumer goods - Moolla, Ahmed I.; Bisschoff, Christo A. (Kamla-Raj, 2012)
This paper develops a model to measure brand loyalty. This is achieved by researching historical brand loyalty models from the literature, and to identify from these models the constructs that influence behaviour related to brand loyalty. An exploratory research perspective examined a broad range of survey-based loyalty influences and then reduced these influences to the twelve more important ones. These twelve influences were further examined and a number of valid questions to measure each influence, were formulated from the literature review. This culminated in the final result, namely the model to measure brand loyalty. The research is of value to management, especially marketing and brand managers, as well as academics and other researchers. Managers will be able to apply the model to determine which specific influences are the most important for their products or services, while also identifying where their brand loyalty fails
Keywords: Managerial Tool; business competitiveness; marketing; brand management; brand loyalty influences